The moral animal : the new science of evolutionary psychology - Wright, Robert, 1957- (Pantheon Books, 1994)
Every so often the world of ideas is shaken by what the philosopher of science Thomas Kuhn famously dubbed a "paradigm shift." As Robert Wright shows in this pathbreaking book, such a shift is occurring now - one that will change the way people see their lives and the way they choose to live their lives.